ISOZYME VARIATION AND TAXONOMIC RANK OF CONTRACAECUM-RADIATUM (V-LINSTOW, 1907) FROM THE ANTARCTIC OCEAN (NEMATODA, ASCARIDOIDEA) - P. Arduino; J. Plotz; P. Orecchia; NASCETTI, Giuseppe; CIANCHI, Maria Rossella; MATTIUCCI, Simonetta; D'AMELIO, Stefano; PAGGI, Lia; BULLINI, Luciano (Systematic Parasitology, 1995)
Genetic variation of the Antarctic anisakid Contracaecum radiatum from the Ross and Weddell Seas is studied at 24 enzyme loci. All polymorphic loci proved to be in Hardy-Weinberg equilibrium, with no significant differences between the samples tested. Several loci were found to be diagnostic between C. radiatum and the five known members of the C. osculatum complex, indicating that no gene exchange occurs between them and confirming their specific status. No F-1 hybrids, recombinant or introgressed individuals, sharing radiatum and osculatum alleles, were detected in the Antarctic Contracaecum samples; this directly proves the reproductive isolation of C. radiatum. Biochemical keys are given for the identification of Antarctic C. radiatum, C. osculatum D and E, both for adults (males and females) and larvae. Higher values of genetic variability were observed in these Antarctic Contracaecum species than in the Arctic-Boreal C. osculatum members, possibly related to a lower degree of habitat disturbance (i.e. by pollution, fishing and hunting) in the Antarctic region. On the basis of genetic distances, the evolutionary divergence between C. radiatum and C. osculatum (sensu late) started about 5 million years ago, possibly with the first colonisation of the Antarctic region by seals. Data on paratenic (fish) and definitive (seal) hosts of C. radiatum and C. osculatum D and E are given.